The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0268355518772760
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the use of deep venous stenting for acute venous thrombosis of the lower limb

Abstract: Objectives The aim is to evaluate venous stent patency, the development of post-thrombotic syndrome, recurrence, quality of life and the optimal post-procedural anticoagulation regimen in the treatment of iliofemoral deep venous thrombosis. Method and results EMBASE and Medline databases were interrogated to identify studies in which acute deep venous thrombosis patients were stented. Twenty-seven studies and 542 patients were identified. Primary, assisted primary and secondary patency rates 12 months after st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
(202 reference statements)
0
13
0
1
Order By: Relevance
“…In the treatment of IVCS, balloon angioplasty is inadequate for treating the venous system, and therefore stent placement is frequently required. 16 Current evidence has shown that stent placement after AngioJet thrombectomy or CDT in individuals with acute lower extremity DVT accompanied with IVCS is safe, efficacious, and durable. 17,18 Therefore, we performed PTA and stent implantation after thrombus removal at the occlusion and stenosis area of outflow.…”
Section: Discussionmentioning
confidence: 98%
“…In the treatment of IVCS, balloon angioplasty is inadequate for treating the venous system, and therefore stent placement is frequently required. 16 Current evidence has shown that stent placement after AngioJet thrombectomy or CDT in individuals with acute lower extremity DVT accompanied with IVCS is safe, efficacious, and durable. 17,18 Therefore, we performed PTA and stent implantation after thrombus removal at the occlusion and stenosis area of outflow.…”
Section: Discussionmentioning
confidence: 98%
“…El tratamiento antiagregante ha demostrado ser seguro y eficaz en pacientes con stent arteriales, pero su efecto en pacientes con stent venosos, con o sin TVP previa, se desconoce. En una revisión realizada en 2018 se observaron grandes diferencias entre diversos estudios a la hora de administrar antiagregante tras la implantación del stent, mientras que en todos los casos se administró terapia anticoagulante [13][14][15] .…”
Section: Discussionunclassified
“…14 Use of antiplatelet agents did not seem to show any significant benefit. 14 Pregnancy in women who have had previous VTE and stenting procedures may need careful consideration. Retrospective data suggest they are not at increased risk of stent occlusion or recurrent VTE during pregnancy or in the postpartum period, 30 but further data are required.…”
Section: Challenges Of Placing Venous Stentsmentioning
confidence: 99%